Faculty and Students: Differing Views of Mentoring at a University Level - Kathleen J. Sanders (The Advocate, 2014)
Although students and faculty at a university level differ on what constitutes mentoring, communication is key. Students and their faculty instructors/advisors in university online programs were surveyed to discover if and how the perceived mentoring occurred. Students wanted evidence of a personal interest in them by their instructors/advisors. However, students equated mentorship with communication. Students were particularly interested in the amount of time delay between any question they asked and the response they received from their instructor/advisor. Faculty considered mentoring to be above and beyond mere advising or instructing in an online course or program. Faculty also perceived communication as vital; but mentorship communication was vital to the professional development of their students/advisees and not simply answers to course or graduation questions.